A Cu / TiO2-EA material, its preparation method and application

CN117733133BActive Publication Date: 2026-10-16FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211468854.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2026-10-16
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

目前大多数用于二维材料表面的后修饰过程都比较暴力且剧烈,会对二维材料的层状结构造成不同程度的破坏,不利于研究材料结构与性能之间的关系,且多数金属氧化物需要在高温条件下才能实现对某一气体的灵敏传感,此外大多数制备原子级分散催化剂采用的技术方法流程都较为复杂,涉及高温煅烧、较高浓度H2还原和硼氢化钠还原等过程,制备成本高且危险系数较高,因此需要寻求一种高性能、工艺简单、安全且经济可行的传感材料制备技术应用于气敏传感器

Benefits of technology

[0047] (1) The preparation method of Cu/TiO2-EA provided in this application adopts a post-synthesis modification method to replace the hydroxyl ligands already coordinated on the surface of ultrathin TiO2 nanosheets with amino ligands. The ligand post-modification of the surface of ultrathin nanosheets is carried out without destroying the original material structure. The amino ligands on the surface of TiO2 nanosheets provide the necessary conditions for anchoring atomically dispersed Cu, thereby realizing the control of the coordination environment on the surface of nanosheets. Furthermore, an economical and low-cost liquid-phase ultraviolet light-assisted method is used to prepare atomically dispersed metal catalysts. Cu atoms are in a stable atomically dispersed state on the surface of TiO2 nanosheets. The overall synthesis and preparation cost is low, the process is simple, environmentally friendly, safe, and economically feasible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117733133B_ABST
    Figure CN117733133B_ABST
Patent Text Reader

Abstract

The application discloses a Cu / TiO2-EA material, which comprises Cu monomers, amino ligands EA and TiO2; the Cu monomers are anchored on the surface of the TiO2 through the amino ligands EA and can be used as a normal-temperature low-concentration gas detection sensor material. The Cu / TiO2-EA material adopts a post-synthesis modification mode to replace the hydroxyl ligands coordinated on the surface of ultrathin TiO2 nanosheets with amino ligands, performs ligand post-modification on the surface of the ultrathin nanosheets without destroying the original material structure, the amino ligands on the surface of the TiO2 nanosheets provide necessary conditions for anchoring atomically dispersed Cu, the regulation of the coordination environment on the surface of the nanosheets is realized, and an economic and low-cost liquid-phase ultraviolet light-assisted method is adopted to prepare an atomically dispersed metal catalyst, the Cu atoms are in a stable atomically dispersed state on the surface of the TiO2 nanosheets, and the overall synthesis and preparation cost is low, the process is simple, the method is environmentally friendly, the safety is high, and the method is economically feasible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a Cu / TiO2-EA material, its preparation method, and its application, belonging to the field of sensor materials technology. Background Technology

[0002] In recent years, chemiluminescent semiconductor metal oxide (SMO) gas sensors have attracted widespread attention in environmental monitoring, medical and health monitoring, and food safety detection due to their advantages of low production cost, high sensitivity, ease of use, and ability to detect various gases. Most single-phase SMOs require thermal activation at temperatures above several hundred degrees Celsius, and their performance in the low-temperature region still needs further improvement. Benefiting from the electronic and chemical sensitization and excellent catalytic properties of noble metals, many studies utilize noble metal loading to improve the gas sensing performance of SMOs. It is well known that in gas sensing processes, only the outermost metal atoms exposed on the metal nanoparticles can interact with gas molecules, while the inner metal atoms encased cannot actually participate in the catalytic process, resulting in wasted atom utilization. Furthermore, the catalytic activity of different crystal facets within the nanoparticles varies significantly, and heterogeneity of catalytic sites leads to differences in selectivity. Considering the scarcity and high cost of noble metals, designing gas-sensitive materials based on noble metal catalysts to construct high-sensitivity, high-selectivity room-temperature gas sensors is significant but challenging.

[0003] In recent years, atomically dispersed metal catalysts (ADMCs) have attracted increasing attention from researchers in the field of semiconductor gas sensing due to their 100% atomic utilization and uniform, tunable coordination environment. Unlike noble metal nanoparticles, each metal atom in an ADMC can be uniformly dispersed on the support surface, resulting in a uniform coordination environment and consistent geometric and electronic configurations, thus greatly enhancing catalytic selectivity. For gas sensing, this facilitates in-depth research into the relationship between sensing selectivity and the structure of active sites, therefore, ADMCs have broad application prospects in the field of gas sensing. Currently, most post-modification processes used on the surface of two-dimensional materials are quite aggressive and violent, causing varying degrees of damage to the layered structure of two-dimensional materials. This is not conducive to studying the relationship between material structure and performance. Moreover, most metal oxides require high-temperature conditions to achieve sensitive sensing of a certain gas. In addition, most of the technical processes used to prepare atomically dispersed catalysts are quite complex, involving processes such as high-temperature calcination, high-concentration H2 reduction, and sodium borohydride reduction. These processes are costly and have a high risk factor. Therefore, there is a need to find a high-performance, simple, safe, and economically feasible sensing material preparation technology for application in gas sensors. Summary of the Invention

[0004] As one aspect of this application, this application provides a Cu / TiO2-EA material, which has Cu metal single atoms anchored in an amino coordination environment on the surface of ultrathin TiO2 nanosheets, and can be used as a sensor material for detecting low-concentration gases at room temperature.

[0005] The technical solution adopted in this application is as follows:

[0006] A Cu / TiO2-EA material, wherein the Cu / TiO2-EA material comprises Cu single atoms, amino ligand EA, and TiO2;

[0007] The Cu single atom is anchored to the surface of the TiO2 via the amino ligand EA.

[0008] Optionally, the Cu / TiO2-EA material has a morphology of nanoflowers.

[0009] Optionally, the nanoflower is composed of nanosheets.

[0010] Optionally, the thickness of the nanosheet is 1 to 2 nm.

[0011] Optionally, the Cu single atom is anchored to the surface of the TiO2 via the amino ligand EA.

[0012] Optionally, the valence state of the Cu single atom is between 0 and +2.

[0013] Cu single atoms have an oxidation state.

[0014] Optionally, the particle size of the Cu / TiO2-EA material is 200–700 nm.

[0015] Optionally, the loading of Cu single atoms in the Cu / TiO2-EA material is 1.5 to 2 wt%.

[0016] According to another aspect of this application, a method for preparing the above-mentioned Cu / TiO2-EA material is provided, comprising the following steps:

[0017] S1. The raw materials containing titanium source, alcohol and water are heated in a closed container to synthesize hydroxyl-coordinated TiO2.

[0018] S2. A mixture I containing the hydroxyl-coordinated TiO2 obtained in step S1, ethylenediamine, and water is subjected to ultrasonic treatment and heated reaction to obtain amino-coordinated TiO2.

[0019] S3. The mixture II containing the amino-coordinated TiO2, copper chloride, and water obtained in step S2 is subjected to ultrasonic treatment and ultraviolet light irradiation for reduction reaction to obtain Cu / TiO2-EA.

[0020] Optionally, in step S1, the titanium source is selected from at least one of titanium tetrachloride, titanium trichloride, tetrabutyl titanate, and tetraisobutyl titanate.

[0021] Optionally, in step S1, the alcohol is selected from at least one of ethylene glycol, glycerol, and polyethylene glycol.

[0022] Optionally, in step S1, the titanium source, alcohol, and water are in a volume ratio of 1:(30-60):(1-2).

[0023] Optionally, in step S1, the preparation process of the raw materials includes adding the titanium source to alcohol and stirring at a speed of 400-800 rpm for 3-8 minutes, and then adding water.

[0024] Optionally, in step S1, the conditions for heating synthesis include: heating to 120-180°C at a heating rate of 1-5°C / min and holding at that temperature for 4-8 hours.

[0025] Optionally, step S1 further includes centrifuging, washing with water and alcohol, and drying at 50-70°C on the product synthesized by heating.

[0026] Optionally, in step S2, the hydroxyl-coordinated TiO2 nanosheet powder, ethylenediamine, and water are mixed in a solid-liquid ratio of 1:(0.035-0.1):(0.9-1.15) mg:ml:ml.

[0027] Optionally, in step S2, the preparation of mixture I further includes grinding the hydroxyl-coordinated TiO2 into powder.

[0028] Optionally, in step S2, the conditions for the heating reaction include reacting at 50–80°C for 6–12 hours.

[0029] Optionally, step S2 further includes centrifuging, washing with water and alcohol, and drying the product after heating and reaction at 50-70°C.

[0030] Optionally, in step S3, the TiO2 nanosheet powder, copper chloride, and water are mixed in a solid-liquid ratio of 1:(0.017~0.035):(0.55~1.15) mg:ml:ml.

[0031] Optionally, in step S3, the preparation of mixture II includes grinding amino-coordinated TiO2 into powder and adding it to a concentration of 8-12 mg / mL while stirring. -1 Add copper chloride solution and water, and stir in the dark for 6–12 hours.

[0032] Optionally, in step S3, the conditions for ultraviolet irradiation are: ultraviolet light wavelength of 320-400 nm and irradiation time of 5-30 min.

[0033] Optionally, step S3 further includes centrifuging, washing with water, washing with alcohol, and drying at 50-70°C on the product after the reduction reaction.

[0034] Optionally, in steps S2 and S3, the ultrasonic treatment time is not less than 3 minutes.

[0035] Optionally, in steps S2 and S3, the ultrasonic treatment time is 3 to 6 minutes.

[0036] The mechanism by which ethylenediamine-modified TiO2 significantly increases the Cu loading content lies in the strong coordination ability of Cu with N. The d orbitals of Cu can accommodate lone pairs of electrons on the amino ligand N, achieving Cu anchorage through strong coordination interactions. The energy and dose input to the system can be controlled by the irradiation time and irradiation power, making it highly operable, simple to control, and low in risk.

[0037] According to another aspect of this application, the application of the above-mentioned Cu / TiO2-EA material and the Cu / TiO2-EA material prepared by the above-mentioned preparation method in a room temperature gas sensor is provided.

[0038] The room temperature is 15–30°C.

[0039] Optionally, the application includes: mixing Cu / TiO2-EA material with a low-boiling-point solvent, grinding for 10-20 minutes to obtain a viscous sensing material, then drop-casting the viscous sensing material onto a substrate electrode, drying it to form a gas-sensitive sensing layer, and obtaining a gas-sensitive sensor device.

[0040] The low-boiling-point solvent is selected from at least one of isopropanol, ethanol, acetone, and methanol;

[0041] Optionally, the substrate electrode is an Al2O3 substrate electrode with Ag-Pd interdigitated electrodes deposited on its surface, the surface of which has a channel width of 200-500 μm.

[0042] Optionally, before drop casting, the base electrode is placed in ethanol and ultrasonically treated for 5-10 minutes, and then the base electrode is cleaned and dried.

[0043] Optionally, the application further includes connecting the gas-sensitive sensor to gold wires via conductive adhesive, and then vacuum drying it at 60–85°C for 4–6 hours to obtain a well-activated / aged gas-sensitive sensor.

[0044] Optionally, the application further includes connecting the gas-sensitive sensor to a sensing test system to obtain a gas-sensitive sensor suitable for room temperature.

[0045] Optionally, the application includes using a gas sensor to detect low concentrations of ammonia at room temperature.

[0046] The beneficial effects that this application can produce include:

[0047] (1) The preparation method of Cu / TiO2-EA provided in this application adopts a post-synthesis modification method to replace the hydroxyl ligands already coordinated on the surface of ultrathin TiO2 nanosheets with amino ligands. The ligand post-modification of the surface of ultrathin nanosheets is carried out without destroying the original material structure. The amino ligands on the surface of TiO2 nanosheets provide the necessary conditions for anchoring atomically dispersed Cu, thereby realizing the control of the coordination environment on the surface of nanosheets. Furthermore, an economical and low-cost liquid-phase ultraviolet light-assisted method is used to prepare atomically dispersed metal catalysts. Cu atoms are in a stable atomically dispersed state on the surface of TiO2 nanosheets. The overall synthesis and preparation cost is low, the process is simple, environmentally friendly, safe, and economically feasible.

[0048] (2) The Cu / TiO2-EA sensing material prepared in this application, when used in a gas sensor, can achieve sensitive and rapid sensing of low-concentration ammonia gas at room temperature, exhibiting excellent chemielectric resistivity gas sensing performance: Cu / TiO2-EA has a wide response range (10-100 ppm) for low-concentration ammonia gas, with a theoretical detection limit down to the ppb level (the theoretical detection limit at the ppb level is 43 ppb), and a fast response speed with a fast response time (2.5 min) and recovery time (5.1 min), good cycling stability, and good performance in the presence of... Figure 12 It exhibits excellent response selectivity and reproducibility for various gases, thereby improving the safety, reliability, sensitivity, and selectivity of ammonia detection.

[0049] (3) The surface ligand post-modification strategy adopted by the technical solution of this application for two-dimensional ultrathin nanosheets does not destroy the structure of two-dimensional materials, which is conducive to studying the relationship between structure and performance. It provides a new direction and strategy for the development and preparation of new chemical resistance gas sensing materials with higher performance, and can also greatly promote the development and application of room temperature gas sensing materials based on atomically dispersed metals. Attached Figure Description

[0050] Figure 1 The powder diffraction (PXRD) patterns of TiO2-EG and TiO2-EA prepared in Example 1 of this application are shown.

[0051] Figure 2 Atomic force microscopy (AFM) images of TiO2-EG and TiO2-EA prepared in Example 1 of this application;

[0052] Figure 3 The powder diffraction (PXRD) patterns of (a) TiO2-EA and (b) Cu / TiO2-EA prepared in Example 1 of this application are shown.

[0053] Figure 4 This is a scanning electron microscope (SEM) image of Cu / TiO2-EA prepared in Example 1 of this application;

[0054] Figure 5 This is a transmission electron microscope (TEM) image of Cu / TiO2-EA prepared in Example 1 of this application;

[0055] Figure 6 XANES diagram of Cu / TiO2-EA prepared in Example 1 of this application;

[0056] Figure 7 This is the EXAFS image of Cu / TiO2-EA prepared in Example 1 of this application;

[0057] Figure 8The room temperature NH3 dynamic working curve of Cu / TiO2-EA prepared in Example 1 of this application;

[0058] Figure 9 Cyclic stability curve of Cu / TiO2-EA prepared in Example 1 of this application with 50ppm NH3;

[0059] Figure 10 The response recovery curve of Cu / TiO2-EA prepared in Example 1 of this application at 50 ppm NH3;

[0060] Figure 11 The NH3 response value-concentration double log plot of Cu / TiO2-EA prepared in Example 1 of this application;

[0061] Figure 12 This is a selectivity diagram of Cu / TiO2-EA prepared in Example 1 of this application for various gases;

[0062] Figure 13 A comparison chart of Cu content measured by ICP in Cu / TiO2-EA prepared in Example 1 of this application and Cu / TiO2-EG in the comparative example;

[0063] Figure 14 The 100ppm NH3 cycling stability curve of Cu / TiO2-EG prepared in Example 1 of this application;

[0064] Figure 15 The Fourier transform infrared (FT-IR) spectra of Cu / TiO2-EA prepared in Example 1 of this application are as follows. Detailed Implementation

[0065] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0066] Unless otherwise specified, all materials used in the embodiments of this application were purchased commercially, and all reagents and pharmaceuticals used were used directly without further purification.

[0067] The instruments, equipment, and main conditions used in this embodiment are as follows:

[0068] Powder X-ray diffraction (PXRD) analysis uses equipment equipped with Cu Kα radiation The one-dimensional array detector was recorded by the Rigaku Smartlab X-ray diffractometer with a step size of 0.02°.

[0069] Scanning electron microscopy (SEM) analysis was performed using a Zeiss-300 instrument from Zeiss, with a voltage of 5.0 kV.

[0070] Field emission transmission electron microscopy (FETEM) analysis was performed using a TALOS F200X G2 instrument with an accelerating voltage of 200 kV.

[0071] Atomic force microscopy (AFM) analysis was performed using a Bruker Dimension ICON instrument in ScanAsyst air mode, with a scan frequency of 1 Hz and 256 lines.

[0072] Fourier transform infrared (FT-IR) spectroscopy analysis was performed using a VERTEX 70 FT-IR spectrometer from Bruker GmbH, Germany, using the KBr pellet method, with scan wavenumbers ranging from 4000 to 400 cm⁻¹. -1 Within the range, the number of scans was 64;

[0073] X-ray photoelectron spectroscopy (XPS) analysis was performed using a Thermo Fisher ESCALAB 250Xi instrument. The test sample was a powder, and the substrate was a conductive carbon adhesive.

[0074] The gas sensing performance data analysis of the device was performed using a Keithley 2602B digital source meter from Keithley, USA, to collect the current values ​​of the sensor in different gases at a test voltage of 5V.

[0075] In the room temperature gas-sensitive sensor performance test, the concentration of various standard gases was 100 ppm, and test gases with different concentration gradients were configured using a dynamic gas mixing mode, with the total gas flow rate controlled at 600 sccm.

[0076] The device's response to the gas is obtained according to the following formula:

[0077] R = (R a –R g ) / R a ×100%

[0078] The formula is used for detecting reducing gases. If detecting oxidizing gases, then R in the formula should be changed. a R g Interchange; R a = Sensor resistance in air, R g = Sensor resistance when exposed to the target gas.

[0079] Example 1: Preparation of Cu / TiO2-EA nanosheets:

[0080] (1) Preparation of ultrathin TiO2 nanosheets (TiO2-EA) for loading metal single atoms

[0081] Step 1: Synthesis of TiO2-EG nanosheets by solvothermal method

[0082] Add 30 mL of ethylene glycol to a 50 mL polytetrafluoroethylene (PTFE) liner. Use a 1000 μL pipette to transfer 1000 μL of TiCl4 and quickly add it to the 30 mL PTFE liner. Simultaneously, mix and stir at 600 rpm for 5 min with a magnetic stirrer. Then add 1 mL of ultrapure water to obtain a mixed solution. Place the PTFE liner containing the above mixed solution into a stainless steel reactor shell and react at 160 °C for 4 hours. The oven temperature control program is set as follows: starting from 30 °C, increase to 160 °C over 2 hours, maintain a constant temperature for 4 hours, and then cool to room temperature over 6 hours. After the reaction, a white precipitate is obtained. Centrifuge in 20 mL centrifuge tubes at 8000 rpm for 5 min each time. Wash twice with water and once with ethanol, then dry in a vacuum oven at 65 °C to obtain a white powder, which is the synthesized ultrathin TiO2 nanosheets with ethylene glycol surface coordination, denoted as TiO2-EG.

[0083] As attached Figure 15 As shown, Fourier transform infrared spectroscopy (FT-IR) results indicate that the obtained TiO2-EG surface is coordinated with a large number of hydroxyl functional groups, and as shown in the attached figure... Figure 1 The powder X-ray diffraction (PXRD) test results show that the crystal form of the obtained TiO2-EG is consistent with that of TiO2(B) with PDF card number 46-1238. Its strongest diffraction peak near 7.5° indicates that it has a large interlayer spacing, and the wide half-width of all diffraction peaks also indicates that the thickness of its nanosheet powder is very thin.

[0084] Step 2: Preparation of TiO2-EA nanosheets by surface modification of TiO2-EG

[0085] The surface-modifying group was controlled to be ethylenediamine group using a post-ligand modification method: 110 mg of white TiO2-EG nanosheets were obtained, ground into a fine powder, and added to a 250 mL round-bottom flask. 100 mL of ultrapure water was added, and the flask was sonicated in a 100% power sonicator for 5 min until the white powder was evenly dispersed. 4000 μL of ethylenediamine was added to the above solution in the round-bottom flask using a 1000 μL pipette. The flask was gently sealed with a rubber stopper and placed in a constant temperature oil bath at 50 °C for 6 hours. After cooling to room temperature, the flask was removed. The nanosheets were centrifuged in 20 mL centrifuge tubes at 8000 rpm for 5 min each time. After washing twice with water and once with ethanol, the nanosheets were dried in a vacuum oven at 65 °C to obtain a light yellow powder, which is TiO2-EA nanosheet with ethylenediamine group as the surface-modifying group, denoted as TiO2-EA.

[0086] Fourier transform infrared spectroscopy (FT-IR) results showed that the obtained TiO2-EA surface had amino coordination, and X-ray photoelectron spectroscopy (XPS) also revealed the presence of nitrogen-containing substances on the surface. (See attached image.) Figure 2 The atomic force microscopy (AFM) test results also show that the thickness of TiO2-EG and TiO2-EA is 1-2 nm, which are ultrathin nanosheets.

[0087] (2) Metal single atoms were loaded onto TiO2-EA nanosheets using a liquid-phase ultraviolet (λ=365nm) light-assisted method.

[0088] Weigh 17.4 mg TiO2 and disperse it in 10 mL of ultrapure water. Place the solution in an ultrasonic cleaner and sonicate for 5 min to disperse it into a white, uniform TiO2 nanosheet suspension. According to the experimental design, with a metal-to-support mass ratio of 5 wt%, add 500 μL of a 10 mg / mL solution to the TiO2-EA nanosheet suspension under magnetic stirring. -1 A CuCl2 solution was prepared, and 4.5 mL of ultrapure water was added. The mixture was stirred for 6 hours at room temperature in the dark until it was homogeneous and saturated with adsorption. The mixed suspension was then exposed to an LED UV lamp with a UV wavelength of 365 nm for UV-assisted anchoring and reduction for 20 min. After centrifugation, washing and drying, a light yellow powder was obtained, which is the TiO2-EA nanosheet with atomically dispersed Cu on the surface, denoted as Cu / TiO2-EA.

[0089] As attached Figures 3-7 As shown, X-ray photoelectron spectroscopy (XPS), synchrotron radiation X-ray absorption spectrometry (XANES, EXAFS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) all demonstrate that Cu is atomically dispersed on the surface of TiO2-EA nanosheets and possesses a certain oxidation state (from...). Figure 6 The XANES pattern of Cu shows that the fingerprint characteristics of the absorption edge of Cu / TiO2-EA are most similar to those of CuO, indicating that the valence state of Cu in Cu / TiO2-EA is closer to +2 rather than 0, and therefore exhibits an oxidation state. Cu maintains a stable atomic-level dispersion on the nanosheet surface through interaction with amino groups on the TiO2-EA surface.

[0090] Example 2: Construction of a gas sensor based on Cu / TiO2-EA nanosheets using the drop casting method.

[0091] (1) Place the Ag-Pd interdigitated electrode with a channel width of 200μm in anhydrous ethanol and sonicate for 5 minutes to clean the surface dirt. Then dry it with a nitrogen gun for later use.

[0092] (2) Take 20 mg of Cu / TiO2-EA powder prepared in Example 1 as the sensing material, add an appropriate amount of isopropanol, grind it in an agate mortar for about 15 minutes to make it into a viscous slurry with fine particles and uniform dispersion, then use a 20 μL pipette to transfer 4 μL and uniformly drop it onto the Ag-Pd interdigitated electrode cleaned in step (1), air dry it at room temperature, and then connect it to the gold wire with conductive silver paste. After the silver paste dries completely, the gas sensor device for testing is obtained.

[0093] (3) Place it in a covered petri dish, dry it in an 80°C vacuum oven to remove the surface isopropanol and activate / age it for 4 hours, then cool it to room temperature and take it out for use.

[0094] Test Example 1: Room Temperature Gas Sensing Performance Test of Cu / TiO2-EA Nanosheets:

[0095] The activated / aged devices prepared in Example 2 were subjected to room temperature (15-30℃) sensing tests. The test operating voltage was 5V, and a dynamic gas mixing mode was used to control the ratio of dry air to standard gas to prepare test gases with different concentration gradients. The total gas flow rate was controlled at 600 sccm. The concentration of all standard gases used in the tests was 100 ppm. The table below shows the preparation ratio of test gases with different concentrations. In the experiment, the gas was mixed according to the ratio in Table 1 to prepare test gases of different concentrations.

[0096] Table 1. Ratio of dry air to standard gas and corresponding concentration of test gas

[0097]

[0098]

[0099] At room temperature, the sensor was placed in an opaque, sealed quartz tube. Gas-sensitive sensing tests were conducted by monitoring the real-time changes in the DC current of the device under different concentrations of the target gas analyte (the gas flow time was set to 5 minutes). Dry air was used as the carrier gas for the analyte, and the device current under dry air was used as the baseline current. When the analyte was introduced, the device current increased or decreased. When dry air was reintroduced, the current returned to the baseline current. The device's response to the absence of gas flow was calculated by monitoring the current change. All tests were performed at room temperature and under no-light conditions.

[0100] The dynamic gas-sensitive response of Cu / TiO2-EA to NH3 concentrations of 5, 10, 30, 50, 70, and 100 ppm was tested at room temperature. The results are as follows: Figure 8As shown, its response value to 50 ppm NH3 at room temperature is [value missing]. Linear fitting of its dual log axis curve yielded a correlation coefficient of 0.984, further demonstrating a strong linear relationship between the response value and the NH3 concentration. Based on the fitted response line, the theoretical detection limit for low-concentration NH3 was calculated to be 43 ppb, using 10% of the response value. The constructed Cu / TiO2-EA gas sensor device, at room temperature, [details missing]. Figures 9-11 As shown, the response value to 50 ppm NH3 is 196%, with response and recovery times of 2.5 and 5.1 min, respectively, and it exhibits good cycling stability. When testing the sensing response of the Cu / TiO2-EA-based sensor to other gases, such as... Figure 12 As shown, it can be seen that it has excellent specific selectivity only for NH3.

[0101] Comparative Example 1: TiO2-EG without ethylenediamine post-modification

[0102] The TiO2-EG nanosheets from Example 1, without ethylenediamine modification, were directly used for loading atomically dispersed Cu. All other conditions remained unchanged except that TiO2-EA was replaced with TiO2-EG. After Cu was anchored under liquid-phase ultraviolet light, the mixture was centrifuged, washed, and dried to obtain a pale yellow Cu / TiO2-EG powder. Figure 13 As shown, ICP test results indicate that, under the same Cu source addition, the actual Cu content of Cu / TiO2-EG obtained by anchoring Cu to the surface with ethylene glycol (0.116%) is much lower than the Cu content of Cu / TiO2-EA obtained by anchoring Cu to the surface with ethylenediamine (1.86%). Room temperature NH3 gas sensing results show that Cu / TiO2-EG has a very low response to 100ppm NH3, and the response decays significantly with increasing test cycles, making it unsuitable as a sensitive material for sensing low-concentration NH3 at room temperature.

[0103] This demonstrates that the post-ligand modification strategy adopted in this work significantly improves the coordination and anchoring ability of two-dimensional nanosheets for Cu atoms without damaging the material structure. Consequently, the prepared Cu / TiO2-EA has more sensing active sites and exhibits better room-temperature NH3 sensing performance (as shown in the attached figure). Figure 9 With appendix Figure 14 The comparison shows that the ammonia sensing performance of Cu / TiO2-EA, which is anchored by ethylenediamine ligand, is much higher than that of Cu / TiO2-EG.

[0104] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A Cu / TiO2-EA material, characterized in that, The Cu / TiO2-EA material comprises Cu single atoms, amino ligand EA, and TiO2; The Cu single atom is anchored to the surface of the TiO2 via the amino ligand EA; The Cu / TiO2-EA material is prepared by a post-ligand modification method, which involves contacting TiO2 nanosheets with hydroxyl-coordinated surfaces with ethylenediamine, replacing the hydroxyl ligands on the surface of the hydroxyl-coordinated TiO2 nanosheets with ethylenediamine, thereby obtaining TiO2 nanosheets with amino-coordinated surfaces, and then anchoring the Cu single atoms onto the amino-coordinated TiO2 nanosheets.

2. The Cu / TiO2-EA material according to claim 1, characterized in that, The loading of Cu single atoms in the Cu / TiO2-EA material is 1.5~2wt%.

3. The Cu / TiO2-EA material according to claim 1, characterized in that, The Cu / TiO2-EA material has a nanoflower morphology.

4. The Cu / TiO2-EA material according to claim 3, characterized in that, The nanoflowers are composed of nanosheets.

5. The Cu / TiO2-EA material according to claim 4, characterized in that, The thickness of the nanosheet is 1~2 nm.

6. The Cu / TiO2-EA material according to claim 1, characterized in that, The Cu single atoms are anchored to the surface of the nanosheet via the amino ligand EA.

7. The Cu / TiO2-EA material according to claim 1, characterized in that, The valence state of the Cu single atom is between 0 and +2.

8. The method for preparing the Cu / TiO2-EA material according to any one of claims 1 to 7, characterized in that, Includes the following steps: S1. Raw materials containing titanium source, alcohol and water are heated in a closed container to synthesize TiO2 nanosheets with hydroxyl coordination. S2. A mixture I containing the hydroxyl-coordinated TiO2 nanosheets obtained in step S1, ethylenediamine, and water is subjected to ultrasonic treatment and heated reaction to obtain amino-coordinated TiO2. S3. The mixture II containing the amino-coordinated TiO2, copper chloride, and water obtained in step S2 is subjected to ultrasonic treatment and ultraviolet light irradiation for reduction reaction to obtain Cu / TiO2-EA.

9. The preparation method according to claim 8, characterized in that, In step S1, the titanium source, alcohol, and water are in a volume ratio of 1:(30~60):(1~2).

10. The preparation method according to claim 8, characterized in that, In step S1, the titanium source is selected from at least one of titanium tetrachloride, titanium trichloride, tetrabutyl titanate, and tetraisobutyl titanate.

11. The preparation method according to claim 8, characterized in that, In step S1, the alcohol is selected from at least one of ethylene glycol, glycerol, and polyethylene glycol.

12. The preparation method according to claim 8, characterized in that, In step S1, the conditions for heating synthesis include: heating to 120-180°C at a heating rate of 1-5°C / min and holding at that temperature for 4-8 hours.

13. The preparation method according to claim 8, characterized in that, The hydroxyl-coordinated TiO2 nanosheets, ethylenediamine, and water are in a solid-liquid ratio of 1:(0.035~0.1):(0.9~1.15) mg:ml:ml.

14. The preparation method according to claim 8, characterized in that, In step S2, the conditions for the heating reaction include reacting at 50~80℃ for 6~12 hours.

15. The preparation method according to claim 8, characterized in that, In step S3, the TiO2 nanosheets, copper chloride, and water are mixed in a solid-liquid ratio of 1 mg:ml:ml (0.017~0.035):(0.55~1.15).

16. The preparation method according to claim 8, characterized in that, In step S3, the conditions for ultraviolet irradiation are: ultraviolet light wavelength of 320~400nm and irradiation time of 5~30min.

17. The preparation method according to claim 8, characterized in that, In steps S2 and S3, the ultrasonic treatment time is not less than 3 minutes.

18. The application of at least one of the Cu / TiO2-EA materials according to any one of claims 1 to 7, and the Cu / TiO2-EA materials prepared by the preparation method according to any one of claims 8 to 17, in a room temperature gas sensor; The room temperature is 15~30℃.

19. The application according to claim 18, characterized in that, The applications include using gas sensors to detect low concentrations of ammonia at room temperature.

Citation Information

Patent Citations

  • Copper monatomic loaded titanium dioxide nanosheet, and preparation method, application and method thereof

    CN114672842A